Super-flexible perovskite solar cells with high power-per-weight on 17 μm thick PET substrate utilizing printed Ag nanowires bottom and top electrodes. (26th July 2019) - Xie, Menglan; Wang, Jie; Kang, Jiachen; Zhang, Lianping; Sun, Xue; Han, Kang; Luo, Qun; Lin, Jian; Shi, Liyi; Ma, Chang-Qi
Abstract: In this work, an ultrathin transparent conductive electrode was developed through inkjet-printing the Ag nanowires (Ag NWs) network on the 17 μ m thick PET substrates. After modifying the Ag NWs with an ammonia and polyetherimine modified high conductive PEDOT: PSS (m-FCE) layer, super-flexible perovskite solar cells were fabricated. In these flexible perovskite solar cells, the m-FCE layer played important roles in improving the mechanical properties of the electrode, smoothing the electrode surface, and as well as passivating the interface reaction, which enables the fabrication of high efficiency super-flexible perovskite solar cells that have an optimized and average performance of 13.32% and 12.91%. This super-flexible perovskite solar cells exhibited an extreme high power per weight of 4.16 W g −1, which may allow its application in space or near space. The inkjet-printed Ag NWs were also used both as the bottom and top electrodes of the flexible semitransparent perovskite solar cells, and achieved an optimized efficiency of 10.49%. This work provided a practical route to fabricate high performance super-flexible thin film photovoltaic cells through full solution-processed method.